Disciplinary Literacy: a Case Study on How Secondary Teachers Engage Students in Disciplinary Discourses - (:unkn) unknown (My University, 2015)
Secondary teachers are currently pressured to address low adolescent literacy rates by adopting disciplinary literacy approaches. While the pressure mounts, direction on how such approaches may be modified to meet the learning objectives of different subject areas is limited. Each subject area will have different Discourses or ways of speaking, writing, listening and thinking about its field, necessitating different literacy strategies for each subject’s curriculum. Successful disciplinary literacy entails learning which strategies and approaches to learning are most effective for student learning for each subject area. In this multi-case study, I observed two high school teachers in Chemistry and Psychology to witness how they modified content area strategies to meet disciplinary literacy demands, and interviewed them about their experiences of this process. Through observations and interviews with the teachers and the curriculum director, a picture emerged of a district that was relaxed in its approach to the challenges of disciplinary literacy reform. Teachers reported that they were not influenced by the district’s disciplinary literacy initiative, but had other sources that guided their best practices to get students actively learning during class. Classroom reform was largely left up to individual teachers. The district’s lack of a clear purpose in its disciplinary literacy initiative created the feeling among teachers that disciplinary literacy was an administrative fad that would pass in time. Recommendations include guidelines for improving students’ collaborative discourse during group activities and suggestions for literacy coaches working with teachers in multiple departments at the secondary level. The enduring question is raised regarding the role of professional organizations in the identification and dissemination of effective disciplinary literacy strategies.
Keywords: Disciplinary Literacy; Science; Secondary; Social Studies